P80 PROGNOSTIC IMPACT OF NEW ONSET ATRIAL FIBRILLATION AFTER SINGLE OR DOUBLE STENT LEFT MAIN BIFURCATION PCI. (18th May 2022) - Rigatelli, G; Zuin, M; Gianese, F; Pastore, G; Zanon, F; Roncon, L
Abstract: Objective: Incidence and prognostic value of new onset atrial fibrillation (NOAF) after single versus double stent strategy in bifurcation Left Main (LM) disease has not been yet investigated. Methods: We retrospectively analysed the procedural and medical data of patients referred to our center for complex LM bifurcation disease, treated using Cross–over provisional stenting, T or T–and–Protrusion (TAP), Culotte, and Nano–inverted–T (NIT) techniques between January 1st, 2008 to May 1st 2018. Multivariate Cox–regression analysis was used to assess the role of different stent strategies, adjusted for confounders, on the risk of NOAF during the follow–up period. Results: Five hundred and two patients (316 males, mean age 70.3±12.8 years, mean Syntax score 31.6±6.3) were evaluated. At a mean follow–up of 37.1±10.8 months (range 22.1–39.3 moths), Target lesion failure (TLF) rate was 10.1%. Stent thrombosis and Cardiovascular mortality were observed in 1.2% and 3.6% in of cases, respectively. NOAF occurred in 23 out of 502 patients (4.6%). Patients with NOAF resulted more frequently female, older, obese, diabetic and more frequently experienced TLF and cardiovascular death. NOAF free survival favoured single versus double stent technique and among double stent techniques NIT compared to the others. Single stent strategy had a lower risk of NOAF compared to double stent technique on multivariate analysis (HR: 1.14, 95% CI: 1.10–1.19, p < 0.001 vs HR: 1.28, 95% CI: 1.23–1.32, p < 0.0001). Conclusions: NOAF in distal LM bifurcation disease treated with PCI had a low incidence but resulted more frequent after double than after single stenting technique and associated with worse outcomes.